Dual-Phase steel reinforcing bars in uncorroded and corroded conditions. (10th September 2019) - Caprili, Silvia; Salvatore, Walter; Valentini, Renzo; Ascanio, Cristiano; Luvarà, Gianbruno
Highlights: Durability problems affect TempCore® reinforcements causing decrease of ductility. Dual-Phase steels show good mechanical properties and durability performance. Mechanical characterization is performed in reference and corroded conditions. Correlation between corrosion entity (mass loss) and residual mechanical properties is analysed. Comparison between ordinary reinforcing steels and dual-phase grades is performed. Abstract: Reinforcing steel bars commonly used for RC buildings are often affected by durability problems caused by exposure to aggressive environmental conditions. Corrosion leads to relevant drops of ductility, in terms of deformation capacity and dissipated energy and number of cycles to failure respectively in case of monotonic and cyclic performance. Eurocodes prescribe the adoption of minimum concrete cover thickness and concrete strength to protect structures and materials against corrosion; such measures represent a tool to limit the effects of environmental attacks, without being able to delete the source of the matter. A valid alternative can be found in the development of new Dual-Phase reinforcing steels that, thanks to their mixed microstructure, are less affected by durability deterioration. In the present paper the results of a wide experimental test campaign on Dual-Phase reinforcing bars in uncorroded and corroded conditions are presented, comparing their performance to traditional TempCore® steel.